Research, Ethics and Risk in the Authoritarian Field - Glasius, Marlies (Springer International Publishing, 2018)
This Open Access book offers a synthetic reflection on the authors' fieldwork experiences in seven countries within the framework of 'Authoritarianism in a Global Age', a major comparative research project. It responds to the demand for increased attention to methodological rigor and transparency in qualitative research, and seeks to advance and practically support field research in authoritarian contexts. Without reducing the conundrums of authoritarian field research to a simple how-to guide, the book systematically reflects and reports on the authors' combined experiences in (i) getting access to the field, (ii) assessing risk, (iii) navigating 'red lines', (iv) building relations with local collaborators and respondents, (v) handling the psychological pressures on field researchers, and (vi) balancing transparency and prudence in publishing research. It offers unique insights into this particularly challenging area of field research, makes explicit how the authors handled methodological challenges and ethical dilemmas, and offers recommendations where appropriate. This book is open access under a CC BY 4.0 license.